Silver Nanoparticles Capped with p-Hydroxybenzoic Acid as a Colorimetric Sensor for the Determination of Paraquat - Gusrizal Gusrizal; Sri Juari Santosa; Eko Sri Kunarti; Bambang Rusdiarso (Universitas Gadjah Mada, 2020)
Highly stable silver nanoparticles capped with p-hydroxybenzoic acid were synthesized by reducing silver ion with p-hydroxybenzoic acid and used for the detection of paraquat. The synthesized silver nanoparticles, which are yellow, exhibited an absorption peak at 420 nm when measured with a UV-visible spectrophotometer due to the surface plasmon resonance. In the presence of paraquat, the color of silver nanoparticles changed from yellow to purple accompanied by the appearance of a new peak at 580 nm in addition to the peak at 420 nm. In order to obtain optimum experimental conditions, temperature, and time of reaction were optimized, and the ratio of absorbance obtained at 580 nm and 420 nm (A580/A420) were monitored. The A580/A420 is proportional to the concentration of paraquat. Under the most favorable condition, the calibration curve showed a high level of linearity ranging from 6.0 × 10–4 to 1.0 × 10–3 M, and the detection limit was found to be 8.30 × 10–6 M. Silver nanoparticles capped with p-hydroxybenzoic acid was found to be useful for the colorimetric determination of paraquat in the aqueous medium.